Tracing the Linguistic Roots of Malay and Batak Languages in Sumatra Island: A Historical Comparative Study - Meliana, Riska; Manalu, Manna Maria Sopiana; Triyono, Sulis (OKARA: Jurnal Bahasa dan Sastra, 2024)
Previous research in comparative historical linguistics has traditionally focused on languages within a single region, overlooking cognate languages in other areas. This study seeks to rectify this by quantitatively and qualitatively describing the kinship between Rejang, Serawai, Lembak (Bengkulu), and Toba, Mandailing, and Nias (North Sumatra) languages. It aims to unearth empirical evidence regarding the timing of divergence between Malay and Batak languages, as well as the grouping of languages and the percentage of kinship between Bengkulu Province and North Sumatra Province. Utilizing Morris Swadesh's lexicostatistics and glottochronology methods, the research evaluates word kinship based on a fundamental 150-word list. Results indicate significant differences among the six languages, particularly with Rejang and Nias displaying low similarity levels, falling below 30% and not even reaching 10%, respectively. The percentage of kinship between local language pairs in Bengkulu and North Sumatra Province averages at 22.66%, classifying them under the "Family stock" category, indicating identical word correlations despite differing phonetic elements. Glottochronological calculations estimate the separation time between Malay and Batak languages to range from 419 to 3,289 BC. This research significantly enhances understanding of regional language kinship and linguistic diversity.